We sang you home ebook - Van Camp, Richard (2016)
A celebration of the bond between parent and child, this is the perfect song to share with your little ones. In this sweet and lyrical picture book from the creators of the bestselling Little You, gentle rhythmic text captures the wonder new parents feel as they welcome baby into the world. Internationally renowned storyteller and bestselling author Richard Van Camp teams up with award-winning illustrator Julie Flett for a second time to create a stunning book for young readers.